Soil Bioengineering to Deal with Soil Erosion and Landslides in Developing Nations - B, Suresh (Technoarete Transactions on Recent Research in Applied Microbiology and Biotechnology, 2022)
The study has focused on the impacts of bioengineering on soil erosion prevention along with lower the risk of landslides that can accelerate the probability of nation progression considering financial benefits of using this technology. Agriculture field of different developed countries are the mostly influenced by the implication of bioengineering. On the other hand, GREEN infrastructure development through the application of bioengineering also has been focused here. Advantages and disadvantages of this technology also have been discussed over here to depict the importance of bioengineering for the development of nations. Road management also has been highlighted in this study to understand the unique characteristic of bioengineering. Basic principles of bioengineering technology have been prioritized here to measure the strength of this technology. Bioengineering practices considering the prevention of soil erosion and landslides also has been described here following the particular steps. Cost effectiveness and long term impact also has been discussed over here to highlight the beneficial aspect of country development including economic strengthening. Keyword : Agriculture, Bioengineering, Soil erosion.